History as Organizing: Uses of the Past in Organization Studies. Issue 12 (December 2018) - Wadhwani, R. Daniel; Suddaby, Roy; Mordhorst, Mads; Popp, Andrew
Research on the "uses of the past" in organizations and organizing is flourishing. This introduction reviews this approach to integrating history into organization studies and explores its paths forward. We begin by examining the intellectual origins of the approach and by defining why and how it matters to the study of management and organizations. Specifically, we emphasize the performative role of history in making and unmaking organizational orders. Next, we elaborate on how the articles in the special issue demonstrate the uses of the past in shaping organizational identity, strategy, and power. We also highlight how this work contributes to our understanding of the socially embedded character of history in organizations by accounting for the role of materiality, intertextuality, competing narratives, practices, and audiences in how the past is used. We conclude by considering four research frontiers particularly worthy of further exploration—the influence of temporal form, the role of non-rational knowledge, the range of methods, and the integration of ethics—in studies of the uses of the past in organizations.